Di Balik Secangkir Kopi: Entrepreneurial Stressors, Well-being, dan Entrepreneurial Resilience Pengusaha Indonesia - Michella Chelsy; Zoel Hutabarat (Jurnal Publikasi Ilmu Manajemen, 2026)
This study examines how personal, social, and occupational stressors affect entrepreneurial resilience through hedonic and eudaimonic well-being among owners and managers of coffee shops in Indonesia. A quantitative, cross-sectional survey involved 400 respondents selected purposively from Cilegon, Serang, Tangerang, Jakarta, Depok, Bekasi, Bandung, and Surabaya. Respondents were directly involved in daily operations and managed businesses that had operated for at least three years. The data were analyzed using partial least squares structural equation modeling with SmartPLS 4. Personal stressors negatively affected hedonic well-being (β = -0.357) and eudaimonic well-being (β = -0.319). Social stressors also reduced hedonic well-being (β = -0.206) and eudaimonic well-being (β = -0.187), while occupational stressors negatively affected hedonic well-being (β = -0.168) and eudaimonic well-being (β = -0.191). Hedonic well-being (β = 0.240) and eudaimonic well-being (β = 0.285) positively affected entrepreneurial resilience. All six indirect effects were significant, confirming that both forms of well-being mediate the influence of the three stressor dimensions on resilience. Eudaimonic well-being displayed the strongest positive importance for resilience, whereas personal stressors represented the most substantial negative pressure. The findings extend entrepreneurial well-being research by separating three stressor sources and two well-being mechanisms. Coffee-shop entrepreneurs should strengthen delegation, workload distribution, social support, recovery time, and a meaningful sense of business purpose to sustain adaptive capacity and business continuity.